Synchronization between two Hele-Shaw Cells - A. Bernardini; J. Bragard; H. Mancini (Mathematical Biosciences and Engineering)
Complete synchronization between two Hele-Shaw cells is examined.The two dynamical systems are chaotic in time and spatiallyextended in two dimensions. It is shown that a large number ofconnectors are needed to achieve synchronization. In particular,we have studied how the number of connectors influences thedynamical regime that is set inside the Hele-Shaw cells.